Gender differences in pharmacokinetics and tissue distribution of 3 perfluoroalkyl and polyfluoroalkyl substances in rats. (November 2016) - Kim, Sook-Jin; Heo, Seo-Hee; Lee, Dong-Seok; Hwang, In Gyun; Lee, Yong-Bok; Cho, Hea-Young
Abstract: The aim of this study was to confirm and investigate the gender differences in pharmacokinetic (PK) characteristics and tissue distribution of 3 perfluoroalkyl and polyfluoroalkyl substances (PFASs) consisted of perfluorooctanoic acid (PFOA), perfluorooctanesulfonic acid (PFOS), and perfluorohexane sulfonic acid (PFHxS) in both male and female rats. For this study, a simultaneous determination method of the 3 PFASs in rat plasma and tissues was developed and validated using a UPLC-MS/MS system. The PK parameters after a single oral or intravenous administration of the 3 PFASs in both rats were calculated using WinNonlin ® software. The mean half-life of the 3 PFASs in female and male rats was in the range of 0.15–0.19 and 1.6–1.8 days for PFOA, 23.5–24.8 and 26.4–28.7 days for PFOS, and 0.9–1.7 and 20.7–26.9 days for PFHxS, respectively. The 3 PFASs were highly distributed in the liver and kidney. These results suggest that there are gender differences in the PKs for PFOA and PFHxS in rats, whereas the PFOS represented no significant gender differences except the Kp value of liver. The validated simultaneous determination method of the 3 PFASs was also within the accepted criteria of the international guidance. Graphical abstract: Highlights: The gender differences in pharmacokinetics and tissue distribution of the 3 PFASs were investigated in rats. PFOA and PFHxS showed significant gender difference in rats. A simultaneous determination method of the 3 PFASs in rat plasma and tissues was developed and validated using UPLC-MS/MS.